The Use of Derivation and Inflection in BCC News's “Tory Gloom Ahead of Triple By-Election Test” - Sari, Fatia Novita; Rudianto, Gaguk (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this research is to examine the process of inflectional affixation and derivation in the BCC news article entitled “Tory Gloom Ahead of Triple By-Election Test.